Multimodal Pedagogy in Project-Based Activities for Esp Classrooms: Does It Affect Student Multimodal Literacy? - Wulandari Putri; Mesa Rahmi Stephani; Andi Suntoda Situmorang; Agus Mahendra (LPPM Universitas Advent Indonesia, 2026)
Technological developments have changed the way students learn from time to time. With the development of technology, learning can no longer depend on one mode alone. Through multimodal pedagogy, student diverse learning styles can be better accommodated. However, research applying multimodal pedagogy in the English for Specific Purpose (ESP) context is not yet adequate. For this reason, this study aimed to construct and apply multimodal pedagogy for ESP classroom, specifically English for Sport students, in project-based activities aimed to improve the student multimodal literacy. Learning was carried out by involving various modes. Meanwhile, the projects were in the form of instructional videos, where the content was related to the student professional targets. This research is quasi-experimental research employing a mixed-method approach involving two English for Sport classes consisting of approximately 120 students. One class was assigned as experiment group and another class was assigned as the control group. Data were obtained from questionnaires, products from student projects, and focus group discussions. The results of the study showed that the multimodal literacy improvement in experimental group was significant. However, the difference between the control and experimental group was found insignificant.